Thermal properties of cubic zincblende thallium-phosphide from quasi-harmonic Debye model approximation - Daoud, Salah (International Journal of Physical Research, 2017)
The thermal properties of cubic zincblende (B3) thallium - phosphide (TlP) compound under high pressure up to 12 GPa have been studied using the quasi-harmonic Debye model approximation. The relative unit cell volume, the isothermal bulk modulus, the first order derivative isothermal bulk modulus, the Debye temperature and the GrÃ¼neisen parameter are studied at zero-temperature and at standard ambient temperature (298 K) respectively. Our obtained values of the different previous quantities are in general in agreement compared to other theoretical data of the literature.